Location, Location, Location? School District, Length of Residence and Attitudes Toward Diversity and Neighborhood Schools in the Upper South. (May 2022) - Alexander, Alyssa J.; Parcel, Toby L.
Attitudes toward diversity and neighborhood schools matter because they underlie many families' decisions for residential location, with consequences for both school systems and students. Case studies of desegregation highlight locational dynamics that influence these outcomes, but differences in theory and methods limit rigorous comparisons among residents across such areas. This study focuses on two under-researched correlates of these preferences toward school assignment models: school district location and length of residence in that district. We evaluate whether school district location and length of residence decrease support for diverse schools and increase support for neighborhood schools, net of numerous controls. We use an innovative new dataset that features opinion polling of respondents' views of public school assignments in Raleigh, NC; Charlotte, NC; Louisville, KY; Rock Hill, SC; and Nashville, TN (5302 cases). We find that compared to having lived in a school district 7 years or less, living in that district over 15 years decreases support for diversity. Furthermore, living all one's life in a district increases support for neighborhood schools. We also find that Charlotte-Mecklenburg, Rock Hill, and Nashville districts are less supportive of neighborhood schools than Raleigh, but that there are also interactive effects between length of residence and school district location. These results shed light on district differences in social forces leading to school resegregation.